Intraindustry Trade between Malaysia and Other Association of South East Asian Nations Countries: A Panel Data Approach - Anuar, Nur Syakina; Ismail, Mohd Tahir (International Review of Management and Marketing, 2017)
This study aims to determine the determinants of intraindustry trade (IIT) between Malaysia and their Association of South East Asian Nations (ASEAN) trade partners by using the panel data approach. Eight ASEAN countries are selected while nine variables are used in this study with the duration of data start from 2000 to 2014. The result shows that fixed effect model is the best model and only three variables are significant at the 5% level of significance. Thus, differences in gross domestic products, foreign direct investment and gross fixed capital are the determinant of IIT between Malaysia and their ASEAN trade partner. Keywords: Intraindustry Trade, Pool OLS, Fixed Effects Model, Random Effects Model, Least Square Dummy Variables JEL Classifications: C01, C23, F12